ChemInform Abstract: Catalytic Enantioselective Conjugate Additions of (pin)B‐Substituted Allylcopper Compounds Generated in situ from Butadiene or Isoprene. Issue 51 (5th December 2016) - Li, Xiben; Meng, Fanke; Torker, Sebastian; Shi, Ying; Hoveyda, Amir H.
Abstract: Multicomponent catalytic enantioselective transformations that entail the combination of butadiene or isoprene (common feedstock), an enoate (prepared in one step) and B2 (pin)2 (commercially available) are presented.